2016
DOI: 10.1016/j.ejmech.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of indole-2-carboxamides bearing photoactivatable functionalities as novel allosteric modulators for the cannabinoid CB1 receptor

Abstract: 5-Chloro-3-ethyl-N-(4-(piperidin-1-yl)phenethyl)-1H–indole-2-carboxamide (ORG27569, 1) is a prototypical allosteric modulator for the cannabinoid CB1 receptor. Based on this indole-2-carboxamide scaffold, we designed and synthesized novel CB1 allosteric modulators that possess photoactivatable functionalities, which include benzophenone, phenyl azide, aliphatic azide and phenyltrifluoromethyldiazrine. To assess their allosteric effects, the dissociation constant (KB) and allosteric binding cooperativity factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Strikingly, the reduced expression of β-arrestin 1 nearly abolished ORG27569-induced ERK1/2 phosphorylation (but not that by CP55940), whereas cotransfection with β-arrestin 2 siRNA did not alter patterns of ERK1/2 phosphorylation (induced by either ligand) compared to those observed by control siRNA transfection. Analogues of ORG27569 are typically comparable (Ahn et al, 2012; Ahn, Mahmoud, Samala, et al, 2013; Ahn, Mahmoud, Shim, et al, 2013; Khurana et al, 2014; Mahmoud et al, 2013; Qiao et al, 2016), but other results have been observed (Gamage, Anderson, & Abood, 2016). …”
Section: Analysis Of Kinase Phosphorylationmentioning
confidence: 88%
See 3 more Smart Citations
“…Strikingly, the reduced expression of β-arrestin 1 nearly abolished ORG27569-induced ERK1/2 phosphorylation (but not that by CP55940), whereas cotransfection with β-arrestin 2 siRNA did not alter patterns of ERK1/2 phosphorylation (induced by either ligand) compared to those observed by control siRNA transfection. Analogues of ORG27569 are typically comparable (Ahn et al, 2012; Ahn, Mahmoud, Samala, et al, 2013; Ahn, Mahmoud, Shim, et al, 2013; Khurana et al, 2014; Mahmoud et al, 2013; Qiao et al, 2016), but other results have been observed (Gamage, Anderson, & Abood, 2016). …”
Section: Analysis Of Kinase Phosphorylationmentioning
confidence: 88%
“…For example, Ross and colleagues used equilibrium binding and kinetic binding assays to evaluate ORG27569 and related compounds and found that they elicit a conformational change that increases agonist affinity for the orthosteric site, although probe dependence was also observed (Baillie et al, 2013; Khajehali et al, 2015; Price et al, 2005). It should be noted that some functional assays show that ORG27569 and several derivatives do not induce G i protein coupling with CB 1 (Ahn et al, 2012; Ahn, Mahmoud, Samala, et al, 2013; Baillie et al, 2013; Khurana et al, 2014; Mahmoud et al, 2013; Price et al, 2005; Qiao et al, 2016) unlike many orthosteric agonists that do (Howlett & Fleming, 1984), but these compounds do induce effects consistent with coupling to the β-arrestin isoforms 1 and 2 (Ahn et al, 2012; Ahn, Mahmoud, Samala, et al, 2013; Ahn, Mahmoud, Shim, et al, 2013; Khurana et al, 2014). …”
Section: Methods Of Allosteric Ligand Binding Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…molecular dynamics simulations) integrating crystal structure information with site-directed mutagenesis which may shed new light on the allosteric binding sites on the CB 1 receptor. Alternatively, photoactivatable analogues of indole-2-carboxamides such as ORG27569 with functionalities such as benzophenone, aliphatic or phenyl azide and phenyltrifluoromethyldiazrine have also been reported which may provide novel tools for mapping the allosteric binding site(s) on the CB 1 receptor (Qiao et al, 2016). …”
Section: Allosteric Binding Site(s) On the Cb1 Receptor?mentioning
confidence: 99%